2020
DOI: 10.24171/j.phrp.2020.11.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Affecting the Elderly’s Use of Emergency Medical Services

Abstract: Elderly adults are the demographic most likely to utilize emergency medical services (EMS). This study aimed to examine the difference in EMS utilization in subgroups of the elderly population by assessing the predictors for using EMS. Methods: Using both descriptive and logistic regression analyses, this study analyses data from the 2014 Korean Health Panel Survey (n = 3,175). Results: It was observed that certain predisposing factors such as age, sex, and marital status were significant predictors of EMS uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(26 reference statements)
1
6
0
1
Order By: Relevance
“…Moreover, the widowed subscribers consumed on average more services than single and divorced individuals, and significantly more than married ones. In this study, marital status was found to be a substantial and significant predictor for medical services demand, with the likelihood of unmarried people to require medical services being higher, as is supported by the literature [18], [20], [21].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, the widowed subscribers consumed on average more services than single and divorced individuals, and significantly more than married ones. In this study, marital status was found to be a substantial and significant predictor for medical services demand, with the likelihood of unmarried people to require medical services being higher, as is supported by the literature [18], [20], [21].…”
Section: Discussionsupporting
confidence: 75%
“…Loneliness among the elderly is associated with less effective disease management, and deterioration is expected to be slower among non-single elderly people due to disease management and their social environment [19]-[21]. It is possible that the lower average of service requests during the first COVID-19 lockdown, as found in the present study, is due to the need for seniors to temporarily move in with their families, thus requiring less external support services.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Community support highlights the particular importance for older adults of information sharing about diseases, informational support for risk factors, advice in dealing with complications, and providing information on available medical resources [ 19 ]. Correspondingly, isolation from social environment was associated with less effective disease management and deterioration [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…An article by Liao and colleagues has found that mutual support between elderly spouses improves lifestyle and reduces complications among chronic patients, especially in the initial prevention phase of disease deterioration [ 26 ]. Older people were found to be more likely to require emergency services among married couples than among unmarried partners [ 27 ]. Older widowed women tend to ignore their deteriorating health, if they do not suffer from a serious medical condition [ 28 ].…”
Section: Introductionmentioning
confidence: 99%